The Effect of Using Story Pyramid Strategy Toward Students’ Reading Comprehension - Lisa Rahmayuni (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This study aims to find out whether using story pyramid strategy can give the significant effect toward students reading comprehension in the eighth grade of MtsS TI Koto Tinggi. This research used experimental research. The total sample was 36 students of VIII A-VIII B classes. The researcher used the purposive sampling in determining the sample because there are only two classes and both are taught by the same teacher. Reading comprehension test is a tool to collected the data. The findings show that three hypotheses (Ha) were accepted. The first, the result of the pre-test and post-test of the experimental class indicated that the tobtained more than the ttable (3.004 > 1.960). Thus, the alternative hypothesis (Ha) was accepted that there was a significant effect of using story pyramid strategy toward students reading comprehension. The second, the result of the post-test experimental class and control class indicated that tobtained (4.820) more than ttable (1.960). Thus, the alternative hypothesis (Ha) was accepted that there was a significant difference between students who are taught b y using story pyramid strategy and without using story pyramid strategy. The last, the result of the post-test of experimental and control indicated that the tobtained more than ttable ( 4.820 > 1.645). It was also found that the students reading comprehension by using story pyramid strategy were better than the students who are not taught by using story pyramid strategy. So, it is proved that using story pyramid strategy can help students to increase their reading comprehension.Tujuan dari penelitian ini adalah untuk mengetahui apakah penggunaan story pyramid strategy ini dapat memberikan pengaruh yang significant terhadap pemahaman membaca siswa di kelas delapan MTsS TI Koto Tinggi. Jenis penelitian yang digunakan adalah penelitian eksperimen. Populasi dalam penelitian ini adalah seluruh siswa kelas delapan di Mts S TI Koto Tinggi. Total sampel dari penelitian adalah 36 siswa yang mana 18 siswa kelas VIII A dan 18 siswa kelas VIII B. Tehnik pengambilan sampelnya menggunakan purposive sampling. Temuan dari penelitian ini menunjukan bahwa, ketiga hipotesis (Ha)nya di terima. Pertama, hasil hitung (tobtained) dari pre-test dan postest kelas eksperimen lebih besar dari ttable, (3,004 > 1960). Jadi, alternatif hipotesis (Ha) diterima yang artinya ada pengaruh penggunaan story pyramid strategy terhadap pemahaman siswa. Kedua, hasil post-test dari kelas eksperimen dan kelas kontrol didaptkan hasil hitung (tobtained) lebih tinggi daripada ttable , (4,820 > 1,960). Maka alternatif hipotesis (Ha) di terima yang mana terdapat perbedaan yang signifikan dari siswa yang diajar menggukan story pyramid strategy dengan yang tidak menggunakan strategi tersebut. Kemudian yang terakhir, hasil dari post-test kedua kelas didapatkan hasil hitung (tobtained) lebih tinggi daripada ttable, ( 4,820 > 1,645). Juga ditemukan bahwa pemahaman siswa yang diajarkan menggunakan story pyramid strategy lebih baik dari siswa yang tidak menggunakan strategi tersebut. Jadi, ini bisa dibuktikan bahwa penggunaan story pyramid strategy ini dapat membantu siswa dalam meningkatkan pemahaman mereka dalam membaca